The E3 Ubiquitin Ligase HAF1 Modulates Circadian Accumulation of EARLY FLOWERING3 to Control Heading Date in Rice under Long-Day Conditions. Issue 10 (21st September 2018) - Zhu, Chunmei; Peng, Qiang; Fu, Debao; Zhuang, Dongxia; Yu, Yiming; Duan, Min; Xie, Weibo; Cai, Yaohui; Ouyang, Yidang; Lian, Xingming; Wu, Changyin
Abstract : An amino acid variation within the interaction domain of EARLY FLOWERING3 with the E3 ubiquitin ligase HAF1 strongly affects the variation in heading date among japonica rice accessions. Abstract: The ubiquitin 26S proteasome system (UPS) is critical for enabling plants to alter their proteomes to integrate internal and external signals for the photoperiodic induction of flowering. We previously demonstrated that HAF1, a C3HC4 RING domain-containing E3 ubiquitin ligase, is essential to precisely modulate the timing of Heading Date1 accumulation and to ensure appropriate photoperiodic responses under short-day conditions in rice ( Oryza sativa ). However, how HAF1 mediates flowering under long-day conditions remains unknown. In this study, we show that OsELF3 (EARLY FLOWERING3) is the direct substrate of HAF1 for ubiquitination in vitro and in vivo. HAF1 is required for maintaining the circadian rhythm of OsELF3 accumulation during photoperiodic responses in rice. In addition, the haf1 oself3 double mutant headed as late as oself3 plants under long-day conditions. An amino acid variation (L558S) within the interaction domain of OsELF3 with HAF1 greatly contributes to the variation in heading date among japonica rice accessions. The japonica accessions carrying the OsELF3(L)-type allele are found at higher latitudes, while varieties carrying the OsELF3(S)-type allele are found at lower latitudes. Taken together, our findings suggest that HAF1 precisely modulates the diurnal rhythm of OsELF3 accumulation to ensure the appropriate heading date in rice.